Encephalomyelitis with seroconversion to Listeria monocytogenes. Issue 9 (September 1991) - Baxter, P; Gardner-Medwin, D; Bates, D; Ragunathan, L; Ingham, H R
Abstract : A previously healthy girl recovered from a lymphocytic encephalomyelitis with brain stem involvement after antibiotic and steroid treatment. Cultures of blood and cerebrospinal fluid were negative, but she seroconverted to Listeria monocytogenes serotype 4. Antilisterial treatment should be considered in similar cases.